The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1021/jp064401y
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Stability, Electron-Transfer Kinetics, and pH-Dependent Energetics of Si/H2O Interfaces through Methyl Termination of Si(111) Surfaces

Abstract: Methyl-terminated, n-type, (111)-oriented Si surfaces were prepared via a two-step chlorination-alkylation method. This surface modification passivated the Si surface toward electrochemical oxidation and thereby allowed measurements of interfacial electron-transfer processes in contact with aqueous solutions. The resulting semiconductor/liquid junctions exhibited interfacial kinetics behavior in accord with the ideal model of a semiconductor/liquid junction. In contrast to the behavior of H-terminated Si(111) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 31 publications
6
60
0
Order By: Relevance
“…However, the band edge positions can remain unchanged by coating the semiconductor with a pH-insensitive organic group. 40 Moreover, the band edges can be directly tuned without altering the semiconductor by forming a dipolar structure at the interface, which is caused by the specific adsorption of ions from the electrolyte. 41 1.3.10.…”
Section: •−mentioning
confidence: 99%
“…However, the band edge positions can remain unchanged by coating the semiconductor with a pH-insensitive organic group. 40 Moreover, the band edges can be directly tuned without altering the semiconductor by forming a dipolar structure at the interface, which is caused by the specific adsorption of ions from the electrolyte. 41 1.3.10.…”
Section: •−mentioning
confidence: 99%
“…7,48 It has been shown that surface grafted molecular layers can tune the band edge position of semiconductor photoelectrode. 49,50 ALD is an excellent process for chemically modifying substrates with sub to monolayers of different molecules. 7,9 This, in principle, can provide beneficial applications in grafting designed functional molecules for tuning surface dipole properties, band edges, and surface state density of the electrodes.…”
Section: Bandgap Engineering For Photoelectrochemical Electrodesmentioning
confidence: 99%
“…As will be seen below, the presence of silica layers at solid/liquid interface confers sensitivity to pH variations. The functionalisation steps, which substitutes silica with other chemical groups may lead to the loss of pH sensitivity and hence to the impossibility to use it for the realisation of potentiometric biosensor (Hamann and Lewis 2006). This is not, in any case, a problem for other types of signal transduction.…”
Section: Psi Surface Functionalisation and Biomolecules Immobilisationmentioning
confidence: 99%